Application of Intent-Analysis to Therapeutic Discourse in the Analysis of the Professional Activity of Psychotherapists - Kirillova, Elena I. (2021)
The paper presents the author's original technique of intent-analysis of psychotherapeutic discourse, alongside the results of the in-depth psychological intent-analysis of Carl Rogers’ psychotherapeutic speech, which was conducted using this technique. This paper includes a dictionary of therapeutic speech intentions, a classification of intentional characteristics of psychotherapeutic speech, some markers of intentions and an instruction for experts. The work includes an analysis of several therapeutic sessions given by Carl Rogers, as compared to those given by novice client-centered psychotherapists; the analysis was carried out using the author’s original methodology (intent-analysis of psychotherapeutic discourse). The developed tools can be significant and useful in the supervision of practicing psychotherapists and the training of novice psychotherapists.